1999
DOI: 10.4269/ajtmh.1999.60.921
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of susceptibility to infection with Ascaris lumbricoides.

Abstract: Abstract. Epidemiologic studies of helminthic infections have shown that susceptibility to these parasites frequently aggregates in families, suggesting the possible involvement of genetic factors. This paper presents a genetic epidemiologic analysis of Ascaris lumbricoides infection in the Jirel population of eastern Nepal. A total of 1,261 individuals belonging to a single pedigree were assessed for intensity of Ascaris infection at two time points. Following an initial assessment in which all individuals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
2
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 36 publications
7
78
2
7
Order By: Relevance
“…The immune system is no exception, and considerable insight may be gained from an ecological, adaptationist perspective. Correspondingly, anthropologists have become increasingly interested in field studies of immunity and their significance to the study of adaptation and human ecology (Barnes et al, 1999;Campbell et al, 2001;Flinn, 1999;Hoff, 1999;Hurtado et al, 1997Hurtado et al, , 2003Lubach et al, 1995;McDade et al, 2000bMcDade et al, , 2001aMcDade and Worthman, 1999;Shell-Duncan, 1993;Shell-Duncan and Wood, 1997;Ulijaszek, 1998;Williams-Blangero et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The immune system is no exception, and considerable insight may be gained from an ecological, adaptationist perspective. Correspondingly, anthropologists have become increasingly interested in field studies of immunity and their significance to the study of adaptation and human ecology (Barnes et al, 1999;Campbell et al, 2001;Flinn, 1999;Hoff, 1999;Hurtado et al, 1997Hurtado et al, , 2003Lubach et al, 1995;McDade et al, 2000bMcDade et al, , 2001aMcDade and Worthman, 1999;Shell-Duncan, 1993;Shell-Duncan and Wood, 1997;Ulijaszek, 1998;Williams-Blangero et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…7 In the present study, we address these issues by (i) assembling the sample reported in our household study 7 into multihousehold extended pedigrees, and (ii) using a variance decomposition method to estimate the effect of shared residence, shared genes, and individual risk factors on variation in fecal egg excretion. The variance decomposition method has been applied successfully to other helminthic infections, notably Ascaris lumbricoides, 16 human hookworm infection, 17 and gastrointestinal nematodes in N'Dama cattle. 18 The current study is the first to use this method to estimate the relative importance of shared residence and additive genetic effects on fecal egg counts during S. mansoni infection.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have demonstrated that there is a substantial genetic component to susceptibility to Ascaris infection in humans (22). The focal population for these studies was the Jirel population of eastern Nepal, a Tibeto-Burman language speaking hybrid group derived from Sherpas and Sunwars approximately 10-11 generations ago (23,24).…”
mentioning
confidence: 99%
“…The focal population for these studies was the Jirel population of eastern Nepal, a Tibeto-Burman language speaking hybrid group derived from Sherpas and Sunwars approximately 10-11 generations ago (23,24). We used data on Ascaris egg counts in a single large pedigree comprising 1,261 members of the Jirel population to determine that genetic factors accounted for approximately 30% (h 2 ϭ 0.291, P Ͻ 0.0001) of the variation in eggs per gram of feces (EPG) as assessed by the Kato-Katz thick smear method (22). Systematic environmental factors accounted for an additional 6% of the variation.…”
mentioning
confidence: 99%